Role of B7H4 and Fas in regulation of trophoblast cells and development of pre-eclampsia: a cross-sectional study - Xiujuan Dong; Cuicui Nie; Yanli Yin; Haixia Xu; Yanxia Zhang; Lihua Han; Congcong Xu (Journal of Obstetrics and Gynaecology)
Background This study aimed to investigate the role of B7H4 and Fas in pre-eclampsia (PE) occurrence and development and reveal its potential mechanisms.Methods Thirty healthy individuals and 60 patients with PE were enrolled in the study. In addition, the clinical characteristics of all participants were collected, including age, gestational weeks at delivery, gestational time, number of births, systolic blood pressure, diastolic blood pressure and foetal weight. The chi-square test was used to evaluate differences in clinical characteristics between the high- and low-expression groups. The expression levels of B7H4 and Fas were analysed using western blotting and real-time quantitative polymerase chain reaction (RT-qPCR). The upstream regulators of B7H4 in trophoblasts were predicted and estimated using a luciferase reporter assay. The proliferation and motility of trophoblasts were assessed using CCK8 and transwell assays, respectively.Results B7H4 and Fas were upregulated in PE (p < 0.05) and showed diagnostic potential with insufficient sensitivity and specificity [B7H4: area under curve (AUC) = 0.790, sensitivity = 65%, specificity = 83.33%; Fas: AUC = 0.717, sensitivity = 68.34%, specificity = 73.33%]. B7H4 and Fas were closely associated with increased blood pressure in patients with PE (p < 0.05), and the combination of B7H4 and Fas increased the diagnostic efficacy (AUC = 0.864), sensitivity (73.33%) and specificity (86.67%). In trophoblast cells, miR-4319 negatively regulated B7H4 and Fas expression as well as cell proliferation, migration and invasion (p < 0.05). Overexpression of B7H4 alleviated the inhibitory effects of miR-4319, which were reversed by Fas knockdown (p < 0.05).Conclusions miR-4319 mediates the progression of trophoblast progression by negatively regulating the expression of B7H4 and Fas. Therefore, B7H4 and Fas may serve as potential biomarkers for the prediction and treatment of PE.